Analysis Implementation Level of Authentic Assessment of Physics Learning Curriculum 2013 Pekanbaru City State High School - Ali, Riri Hardiyanti; Zuhelmi, Zuhelmi; Nor, Muhammad; Islami, Nur (Proceedings of the UR International Conference on Educational Sciences, 2018)
The objective of this study is to describe the implementation of autenthic assessment in physics learning class X SMA in Pekanbaru. The study was conducted from May up to June 2017. Quantitative approach used in this survey research. The subjects of the study were 7 teachers who taught physics class X at SMAN 1 Pekanbaru, SMAN 2 Pekanbaru, SMAN 8 Pekanbaru, SMAN Plus Provinsi Riau and SMA BabussalamPekanbaru. The instrument used questionnaires implementation of autenthic assessment. Data analysis technique was descriptive analysis. The result showed that the percentage of autenthic assessment in three aspects such as affective aspect obtained percentage of implementation 79.69%, cognitive aspect obtained 75.51% and psikomotor assessment aspect obtained percentage of implementation 76.98%. Three aspects of the research (affective, cognitive and psikomotor) are included in good level. It can be concluded that authentic assessment implementation based on kurikulum 2013 class X SMA in Pekanbaru in good level with percentage 78.71%.